Comparative appendicular osteology of Tor spp. (Cyprinidae) in Indonesia - Yusrizal Akmal; Muchammad Yunus; Hani Plumeriastuti; Yeni Dhamayanti; Irfannur Irfannur; Arief Hidayat Zulkifli; Muliari Muliari; Agung Setia Batubara (Depik, 2024)
Tor tambroides, T. tambra, T. douronensis, and T. soro are native fish species to Indonesia with their natural habitat generally being upstream of rivers in hilly areas with clear water and strong currents. Information of the structure and function of appendicular osteology is necessary to understand how fish accelerate and maintain body balance in the water. This study used 5 samples per fish species obtained from Tor fishermen around the habitat of these fish. The results of the comparison showed morphological differences between the appendicular structure of Tor species, consisting structure of the pinnae pectoralis, pinnae pelvicalis, pinnae dorsalis, pinnae analis, and pinnae caudalis. The highest variation was found in the pinnae caudalis. The pointed shape of the pinnae caudalis with long fin rays indicates that the Tor species is capable to swim at a high speeds.Keywords:ossa appendiculareTor douronensisTor tambraTor tambroidesTor soro